2017
DOI: 10.1002/jsfa.8547
|View full text |Cite
|
Sign up to set email alerts
|

Graded replacement of maize grain with molassed sugar beet pulp modulated ruminal microbial community and fermentation profile in vitro

Abstract: Results suggest positive effects of the replacement of MG by Bp especially in terms of stimulating ruminal acetate and propionate fermentation. However, high replacement rates of Bp resulted in lowered utilization of ammonia and higher ruminal methane production. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
4
5
0
Order By: Relevance
“…Comparatively less research attention, however, has been dedicated to rumen microbial changes on beet pulp-based diets and to our knowledge, no studies have utilized BP as a replacement for forage in the diet and compared differences in the microbial profiles. Studies have instead focused on using BP as a highfiber/low-starch energy source to replace starchy concentrate feeds (Zhao et al, 2013;Münnich et al, 2018). Nonetheless, these studies have still observed reductions in fiber-degrading bacterial populations in response to BP treatment, which is consistent with our findings (Zhao et al, 2013;Münnich et al, 2018).…”
Section: Dietsupporting
confidence: 87%
See 1 more Smart Citation
“…Comparatively less research attention, however, has been dedicated to rumen microbial changes on beet pulp-based diets and to our knowledge, no studies have utilized BP as a replacement for forage in the diet and compared differences in the microbial profiles. Studies have instead focused on using BP as a highfiber/low-starch energy source to replace starchy concentrate feeds (Zhao et al, 2013;Münnich et al, 2018). Nonetheless, these studies have still observed reductions in fiber-degrading bacterial populations in response to BP treatment, which is consistent with our findings (Zhao et al, 2013;Münnich et al, 2018).…”
Section: Dietsupporting
confidence: 87%
“…Studies have instead focused on using BP as a highfiber/low-starch energy source to replace starchy concentrate feeds (Zhao et al, 2013;Münnich et al, 2018). Nonetheless, these studies have still observed reductions in fiber-degrading bacterial populations in response to BP treatment, which is consistent with our findings (Zhao et al, 2013;Münnich et al, 2018). These results suggest that the optimal type of fiber substrate likely differs between various bacterial populations involved in its breakdown and that fibrolytic species may not be supported as adequately by non-forage fiber sources.…”
Section: Dietsupporting
confidence: 84%
“…A low ruminal pH is strongly associated with high-grain feeding (Zebeli et al, 2008a), possibly resulting in SARA, which is defined as intermittent drops below pH 5.8 for more than 5.24 h per day (Zebeli et al, 2008b) or below pH 6.0 if measured in the reticulum with indwelling sensors (Neubauer et al, 2018). A previous in vitro study found that the replacement of corn grain with Bp does not reduce the fermentative activity in the rumen and the amount of SCFA produced (Münnich et al, 2018b). Thus a similar acidic potential can be assumed, which confirms the results found by Voelker and Allen (2003b), who found no difference in ruminal pH when diets with varying proportions of Bp and corn were fed.…”
Section: Effects On Rumination and Reticuloruminal Phmentioning
confidence: 99%
“…However, Pragya (2016) reported that by replacing maize fodder with different levels of sugar beet pulp (0:100, 20:80, 40:60, 60:40, 80:20 and 100:0), there was increase (P<0.05) in butyric acid proportion with increased level of sugar beet pulp. In other study, Munnich et al (2017) reported that there was increased proportion of butyric acid when maize grains were replaced with sugar beet pulp.…”
Section: Individual Volatile Fatty Acidsmentioning
confidence: 92%
“…However, acetic acid in concentrate mixture 4 (60% DSBP) and concentrate mixture 5 (80% DSBP) was similar. However, Munnich et al (2017) reported that acetic acid concentration was not affected when maize grains were replaced with dried sugar beet pulp. In other study, Pragya (2016) reported that the production of acetic acid increased (P<0.05) with increased supplementation of ensiled sugar beet pulp replacing maize fodder in vitro.…”
Section: Individual Volatile Fatty Acidsmentioning
confidence: 99%